Pengaruh Kadar Filler Kitosan Dan Plasticizer Gliserol Terhadap Sifat Dan Morfologi Bioplastik Berbasis Pati Sagu - Ummy Aisyah Rochaeni; Irdoni HS; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Bioplastic can be made from renewable materials like starch. Properties of sago starch based bioplastic is to be improved by addition of filler and plasticizer. The aim of this research is to know the effect of addition of chitosan filler and glycerol plasticizer to the properties of tensile strength, elongation at break, water absorption and biodegradation from sago starch. In this research with casting method of making bioplastic with starch 10 gr. Furthermore, variations of chitosan filler (2, 3 and 4%w/w), glycerol (3, 4 and 5 ml) and varieties of starch heating temperature (75, 80 and 85C). The bioplastics were characterized by tensile strength, elongation, water uptake, biodegradation, SEM (Scanning Electron Microscopy) and analyzed by using Design Expert v10.0.1. The most significant factor for all responses was the composition of chitosan filler followed by glycerol and temperature. On the best process conditions (chitosan filler 4.68% w/w at 80°C with 4 ml glycerol) was obtained the best response value for tensile strength 9.96 MPa, elongation 17.89%, water absorption 10.95% and biodegradation 40.02%.Keywords : bioplastic, chitosan, glycerol, mechanical properties, sago starch.